Comparison of the effects of midazolam and dexmedetomidine on cognitive functions, anxiety and hemodynamics in fiber optic bronchoscopy (Annals of Medical Research, 2021)
Aim: Fiber optic bronchoscopy (FB) is an invasive method used in the diagnosis and treatment of lung diseases. There are several different sedation guidelines for FB, all of which are used by different healthcare providers. We aimed to compare the sedative effects of midazolam and dexmedetomidine in FB, together with their effects on cognitive functions, hemodynamic parameters, and patient satisfaction and anxiety. Material and Methods: The study includes a total of 80 randomly selected subjects aged ≥ 18 years. The subjects were divided into two groups: midazolam (n = 40) and dexmedetomidine (n = 40). We evaluated treatment outcomes using hemodynamic findings, the Mini-Mental State Examination, the State Anxiety Inventory, and a survey form.Results: The two groups were not significantly different in terms of systolic blood pressure, diastolic blood pressure, mean arterial pressure, heart rate, and peripheral oxygen values. Patient and medical professional satisfaction levels were significantly higher in the dexmedetomidine group. The cognitive functions and anxiety levels both before and after the intervention were similar for the two groups.Conclusion: We conclude that dexmedetomidine can be used safely for sedation in fiber optic bronchoscopy and is preferable to midazolam.
Keywords: Anxiety; bronchoscopy; dexmedetomidine; hemodynamics; midazolam